Optimization of total focusing sparse array imaging based on the zero-crossing factor - Wang, Peng; Wang, Jue; Chen, Sirui; Tong, Lin; Li, Qianwen; Wang, Kunlin; Shen, Yue; Wang, Ping (Measurement : journal of the International Measurement Confederation, 2025)
•Sparse array imaging was researched, and it was found that when the sparsity is 25 %, the imaging efficiency can be greatly improved while the imaging quality is guaranteed.•An ultrasound total focusing sparse array imaging algorithm based on zero-crossing factor (ZCF) and coherent energy coefficient of echo data is proposed.•Significantly improves imaging quality by integrating coherence characterized by zero number of crossings and coherent energy weighting mechanisms. The total focusing method requires the acquisition and processing of a large amount of data, which limits its application in the field of nondestructive testing, which requires real-time performance. To enhance the implementation efficiency of the total focusing method (TFM) while maximizing ultrasonic detection performance and imaging quality, this paper introduces the array sparsification method into TFM. Based on the Field II ultrasonic simulation platform, the variation trend of the sparse TFM is systematically researched as the number of transmitting array elements decreases. To further enhance the imaging quality, this paper utilizes the zero-crossing count in the echo data to characterize signal coherence and employs coherent energy weighting on the imaging data, thereby achieving significant improvement in imaging performance. The experiments employ a 20# steel test block, an aluminum test block, and a practical rail test block to validate the algorithm’s effectiveness. The results demonstrate that, compared to the delay-and-sum (DAS) method, the proposed zero-crossing factor (ZCF) method achieves a 102.85 % improvement in contrast ratio (CR) and an 85.70 % reduction in array performance index (API) for the 20# steel test block. In the aluminum test block experiment, it reduces API by 93.95 % and increases CR by 84.91 %. For the steel rail inspection scenario, CR is enhanced by 132.54 % while API is decreased by 83.81 %. Although the computational complexity of the proposed ZCF algorithm is higher, it achieves substantial improvements in imaging quality.